Efektivitas Kebijakan Pelaksanaan Kegiatan Reses Anggota Dewan dalam Menampung Aspirasi Masyarakat di Provinsi Jawa Timur - Fiqi Nurman Gazali; Sri Kamariyah; Ika Devy Pramudiana; Kristyan Dwijosusilo (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research aims to determine the effectiveness of the policy for implementing recess activities for council members in accommodating the aspirations of the community in East Java Province, based on the perspective of effectiveness theory. The recess is a formal mechanism designed to bring the legislature closer to the community in order to absorb input and hopes that can be integrated into the legislative and budgeting process. This study identified four main aspects of effectiveness: goal achievement, efficiency, relevance, and policy impact. Using qualitative research analysis and data collected through in-depth interviews, observation, and document analysis. The research results show that even though research is an important means for the community to convey needs, its implementation still faces obstacles, such as violations of follow-up to aspirations that have been received and a mismatch between community priorities and the development programs being implemented. This research provides encouragement for follow-up mechanisms and increasing legislative capacity in managing community aspirations so that res activities are more effective and relevant in supporting development at the regional level.